Editorial: infections and hepatic encephalopathy–does the chicken or the egg come FIRST? A novel perspective at the horizon. Issue 6 (4th March 2022) - Riggio, Oliviero; Ridola, Lorenzo
LINKED CONTENT: This article is linked to Alabsawy et al papers. To view these articles, visit https://doi.org/10.1111/apt.16790 and https://doi.org/10.1111/apt.16829